Narratives of Salem bin Zarir Abi Yunus Al-Atari in the Books of the Sunnah, Collection and Study (Islamic Sciences Journal, 2023)
This is a research in which I collected, what I found, from the translation and narrations of Salm bin Zarir Abi Yunus al-Atari Al-Basri, t. 160 AH.1- I did not find the year of the birth of Salam bin Zarir, but it appears that he was born before the year one hundred, and his death was in the year one hundred sixty.2- He narrated seven traces, which are in the degree of acceptance, except for one trace that is weak and the weakness of it is from others, and another trace that I did not find its sustenance.3- The ranks and divisions of the speakers in the narrators should be taken into account. When studying a questionable narrator.4- One of the aims of the modernists in classification is to collect the narration of someone whose narration is characterized by a smile; such as, scarcity and shortage.
Keywords: Al-Atari, the missed prayer, the voluntary prayer, the chapter on medicine, the prohibition of lying, the prohibition of selling weapons .